Effects of Doped Dodecyl Trimethylammonium Bromide Surfactant on Synthesis and Performance of Nanoporous TiO2-SiO2/Chitosan - Rilda, Yetria; Alif, Admin; Munaf, Edison; Salleh, Baharuddin; Krista, Stefani (Asian Journal of Chemistry, 2015)
Nanoporous TiO2-SiO2/chitosan was synthesized via a sol-gel process under controlled sol-gel time. Titanium tetraisopropoxide (TTIP) and tetraethoxy ortho silicate (TEOS) were used as precursors with doped chitosan and dodecyl trimethylammonium bromide (DTAB) surfactant as a template of nanoporous in isopropanol solutions. The effects of various sol-gel times and surfactant DTAB were focused on investigated reviews that their nanoporous character and distribution were more homogeneous than without surfactant DTAB. The properties of these TiO2-SiO2/chitosan materials, characterized from the synthesis results in optimum sol condition during 5-8 h and gellation time during 10-15 h characterized with XRD showed that the crystal phase with hexagonal geometry (101) of crystal phase were anatase with their average crystal size to 9.6-18.2 nm. The FT-IR spectrum showed the interaction of Ti-O-Si occurred in the fingerprint was 960 cm-1. SEM-EDX analysis showed spherical particles, porous and homogeneous distribution with different elements of the composition of the modified stoichiometry. BET and BJH analysis showed the specific surface area was 179.3 m2/g, pore volume 0.2 cm3 g-1 and pore diameter was 45.40 Å. Analysis of UV-visible spectroscopy revealed the values of energy gap (Eg) were 1.7-1.9 and thus showed that the material was effective to be applied in tropical environments where visible light is usually dominant.